Adsorption sheet, adsorption element, and adsorption processing device using the same

By combining the porous metal complex with fibers and a high melting point organic binder, the adsorption sheet made solves the problems of the existing adsorption sheet lacking elasticity and processability, and achieves excellent softness, processability and sufficient adsorption performance.

CN115087499BActive Publication Date: 2025-02-28TOYOBO CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202180011264.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-07-08
Filing Date
2021-01-27
Publication Date
2025-02-28
Estimated Expiration
2041-01-27

AI Technical Summary

Technical Problem

The existing adsorbent sheets lack elasticity and processability during use, resulting in problems such as honeycomb processing time periods in applications such as filters.

Method used

A combination of porous metal complexes and unfibrillated and fibrillated fibers is used to combine with high melting point organic adhesive to make a load-bearing and flexible adsorbent sheet.

Benefits of technology

The adsorbent sheet is achieved with excellent flexibility and processability, and has sufficient adsorption properties, which solves the problem of the adsorbent sheet lacking elasticity and processability in the original technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The adsorption sheet of the present invention contains a porous metal complex and non-fibrillated fibers and fibrillated fibers, wherein the porous metal complex has a metal and an organic ligand, and has a moisture adsorption rate of 30% by mass or more at 25° C. and a relative pressure of 0.5. As a result, the porous metal complex has excellent loading capacity and the sheet has excellent softness and processability, and can exert sufficient adsorption performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an adsorption sheet and an adsorption element for efficiently separating and recovering or adsorbing and removing adsorption target substances such as water, organic solvents, and malodorous components, and an adsorption treatment device using the same. Background Art

[0002] Porous materials such as activated carbon, silica gel, and zeolite are used for various purposes such as deodorization, purification of air and water, separation and refinement of gases, and are indispensable materials for modern life. In recent years, porous materials that combine metal ions that can take various coordination forms with cross-linked ligands with more than two teeth and self-assemble have been discovered, namely new porous materials called porous metal complexes (MOFs) or porous coordination polymers (PCPs). These porous metal complexes have characteristics that existing porous materials such as activated carbon, silica gel, and zeolite do not have, namely, high specific surface area, sharp pore distribution, and high structural design, and therefore have attracted attention.

[0003] As such porous metal complexes, for example, Patent Document 1 discloses that a specific dicarboxylic acid metal complex is suitable as a gas storage material, particularly a storage material for a gas having methane as a main component. In addition, Patent Document 2 discloses a porous metal complex synthesized from copper ions and trimesic acid, and discloses an adsorbent as an example of its use. Furthermore, Patent Document 3 discloses that a porous metal complex obtained from metal chromium or a chromium salt and trimesic acid is particularly excellent as a water vapor adsorbent.

[0004] Such porous metal complexes have the potential to be used as adsorbents for various gases. When used as adsorbents, it is preferred to form the porous metal complexes in powder form into an adsorbent element suitable for use so that it can contact with the operating fluid with less pressure loss. For this purpose, it is increasingly important to establish sheet technology.

[0005] Therefore, Patent Document 4 discloses, as a sheet material containing a porous metal complex, an adsorption sheet containing a porous metal complex, heat-resistant fibers, clay mineral fibers having self-consolidation properties, and an organic binder.

[0006] Prior art literature

[0007] Patent Literature

[0008] [Patent Document 1] Japanese Patent Publication No. 2001-348361

[0009] [Patent Document 2] Japanese Patent Publication No. 2000-327628

[0010] [Patent Document 3] Japanese Patent Publication No. 2007-51112

[0011] [Patent Document 4] Japanese Patent Publication No. 2013-154301 Summary of the invention

[0012] Problems to be solved by the invention

[0013] However, the adsorption sheet disclosed in Patent Document 4 requires clay mineral fibers, and accordingly, since the content ratio of heat-resistant fibers is reduced, the sheet itself has no elasticity, and there are problems such as lack of sections during honeycomb processing when used as a filter.

[0014] Therefore, an object of the present invention is to provide an adsorption sheet and an adsorption element having excellent supporting properties for a porous metal complex and excellent flexibility and processability of the sheet and sufficient adsorption performance, and an adsorption and desorption treatment apparatus using the same.

[0015] Means to solve problems

[0016] The inventors of the present invention have studied intensively to solve the above problems and have finally completed the present invention. That is, the present invention is configured as follows.

[0017] [1] An adsorption sheet characterized by comprising a porous metal complex and unfibrillated fibers and fibrillated fibers, wherein the porous metal complex has a metal and an organic ligand and has a moisture adsorption rate of 30% by mass or more at 25°C and a relative pressure of 0.5.

[0018] [2] The adsorption sheet according to item 1 above is characterized in that it contains an organic binder having a dissolution temperature in water of 65°C to 100°C.

[0019] [3] The absorbent sheet according to 1 or 2 above, wherein the relative tensile elongation is 5%·m / g or more.

[0020] [4] The adsorption sheet according to any one of 1 to 3 above, characterized in that it contains 60 to 85% by mass of the porous metal complex.

[0021] [5] An adsorption element characterized by comprising the adsorption sheet according to any one of 1 to 4 above.

[0022] [6] An adsorption and desorption treatment device, characterized in that it comprises the adsorption element 5 above, an adsorption device for introducing an adsorption target substance into the adsorption element to adsorb it, and a desorption device for desorbing the adsorption target substance adsorbed by the adsorption element, and continuously performs adsorption and desorption of the adsorption target substance.

[0023] Effects of the Invention

[0024] With the above-mentioned configuration, it is possible to provide an adsorption sheet or the like which is excellent in supporting properties of a porous metal complex and in flexibility and processability of the sheet and has sufficient adsorption performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0025]

Figure 1

[0026]

Figure 2

[0027]

Figure 3

[0028] Explanation of Reference Numerals 1: adsorption sheet, 2: adsorption rotor, 3: motor, 4: high humidity gas, 5: dehumidified gas, 6: low humidity gas, 7: humidified gas, 8: heat source, 9: fan, 10: dehumidification / humidification area switching member, 11: dehumidification air conditioning system DETAILED DESCRIPTION

[0029] Hereinafter, the present invention will be described in detail.

[0030] The adsorbent sheet of the present invention contains a porous metal complex and unfibrillated fibers and fibrillated fibers. The porous metal complex has a metal and an organic ligand and has a water adsorption rate of 30% by mass or more at 25° C. and a relative pressure of 0.5.

[0031] Here, the pressure at which the adsorption process stops (the number of adsorbed molecules = the number of desorbed molecules) under a certain pressure is called the adsorption equilibrium pressure, and the relative pressure refers to the ratio of the adsorption equilibrium pressure to the saturated vapor pressure.

[0032] Since the adsorption sheet of the present invention contains a porous metal complex, it is possible to obtain a higher adsorption performance. In addition, since the porous metal complex is characterized in that the moisture adsorption rate at 25°C and a relative pressure of 0.5 is 30% by mass or more, the sheet itself can retain a lot of moisture, and high flexibility can be obtained during sheet processing. Furthermore, since the porous metal complex can fully exhibit flexibility, the organic binder used to impart flexibility can be reduced, and as a result, the proportion of adsorption (pore clogging) of the side chains of the organic binder in the pores of the adsorbent material can be reduced, and further sufficient adsorption performance can be obtained. If the moisture adsorption rate is less than 30% by mass, the flexibility is poor.

[0033] Furthermore, the adsorption sheet of the present invention contains unfibrillated fibers and fibrillated fibers. By containing unfibrillated fibers, for example, the segment shape can be maintained by itself during segment processing, and the processability is excellent. In addition, by containing fibrillated fibers, the porous metal complex particles can be effectively retained, not only the loadability is excellent, but also the organic binder used to impart loadability can be reduced. As a result, the clogging of pores can be reduced, and sufficient adsorption performance can be further obtained.

[0034] Furthermore, the adsorption sheet of the present invention may also contain a high melting point organic binder having a dissolution temperature in water of 65°C to 100°C. By using a high melting point organic binder having a dissolution temperature in water of 65°C to 100°C, pore clogging can be further reduced, thereby obtaining excellent adsorption performance. When the dissolution temperature in water is less than 65°C, the adsorption performance becomes insufficient due to pore clogging, and at a high temperature of more than 100°C, the loadability is poor due to insufficient bonding.

[0035] The porous metal complex involved in the present invention is a porous material composed of a compound having metal ions and organic ligands. The form of the porous metal complex that can be used is not particularly limited, and powdered or granular materials can be used. Preferred is a porous metal complex with an average particle size of 0.1μm to 200μm, more preferably 1 to 100μm, and most preferably 1 to 80μm. If the average particle size is less than 0.1μm, it will become a cause of reduced yield in adsorption sheeting. In addition, if the average particle size is greater than 200μm, it is sometimes difficult to fully load the porous metal complex on the adsorption sheet, and the porous metal complex will fall off more. The average particle size can be measured, for example, using a scanning electron microscope.

[0036] The BET specific surface area of ​​the porous metal complex measured by a 77K nitrogen adsorption method is not particularly limited, but is preferably 500 m 2 / g or more. If the BET specific surface area is less than 500m 2 / g, it is sometimes difficult to obtain sufficient adsorption performance. The BET specific surface area is more preferably 1000m 2 The upper limit of the BET specific surface area is not particularly limited, but is preferably 6000 m 2 / g or less. If the amount is greater than this range, the production of the porous metal complex becomes very difficult. In addition, the BET specific surface area can be measured by the method described in the following examples, for example.

[0037] The metal ions constituting the porous metal complex are not particularly limited, and examples thereof include typical metal elements such as aluminum ions, and transition metal elements such as titanium ions, zirconium ions, iron ions, and copper ions. On the other hand, examples of compounds having ligands include fumaric acid, 2-aminoterephthalic acid, 1,4-naphthalene dicarboxylic acid, terephthalic acid, and trimesic acid. Specific examples of the porous metal complex include a porous metal complex composed of aluminum ions and terephthalic acid (Basolite A100 manufactured by BASF), a porous metal complex composed of copper ions and trimesic acid (Basolite C300 manufactured by BASF), a porous metal complex composed of iron ions and trimesic acid (Basolite F300 manufactured by BASF), a porous metal complex composed of titanium ions and terephthalic acid, a porous metal complex composed of zirconium ions and terephthalic acid, a porous metal complex composed of zirconium ions and fumaric acid, a porous metal complex composed of zirconium ions and 2-aminoterephthalic acid, and a porous metal complex composed of titanium ions and 2-aminoterephthalic acid. Even if these porous metal complexes are the same porous metal complexes, the BET specific surface areas vary due to the synthesis method and purity. However, in order to give the adsorption sheet flexibility, the water adsorption rate at 25°C and a relative pressure of 0.5 is preferably 30% by mass or more, more preferably 35% by mass or more, and further preferably 40% by mass or more. When it is less than 30% by mass, in order to give the adsorption sheet sufficient flexibility, the content of the organic binder needs to be increased. When the content of the organic binder is high, the proportion of the side chains of the organic binder adsorbed in the pores of the adsorbent material is high, and as a result, the adsorption performance cannot be fully exerted.

[0038] The content of the porous metal complex in the adsorption sheet of the present invention is preferably 60% to 85% by mass, more preferably 65% ​​to 80% by mass. When the content is less than 60% by mass, it is sometimes difficult to obtain sufficient adsorption performance. On the other hand, if the content is greater than 85% by mass, it is difficult to fully load the porous metal complex on the adsorption sheet, and the amount of shedding becomes large. In addition, the sheet strength may also be significantly reduced.

[0039] The fiber diameter of the unfibrillated fiber is preferably 5 μm or more, more preferably 5 μm to 30 μm. In addition, the fiber length is preferably 1 mm to 10 mm, more preferably 2 mm to 8 mm. When the fiber diameter of the coarse fiber is less than 5 μm and the fiber length is less than 1 mm, the strength of the sheet is reduced, and it is difficult to maintain the segment shape after segment processing. In addition, it is difficult to process it into an adsorption element such as a honeycomb in post-processing. In addition, if the fiber diameter of the unfibrillated fiber is greater than 30 μm and the fiber length is greater than 10 mm, it does not have flexibility and processing becomes difficult. Fibers with different fiber diameters can also be further mixed.

[0040] Examples of the non-fibrillated fibers include inorganic fibers such as glass fibers, ceramic fibers, and rock wool fibers; synthetic fibers such as aramid fibers, meta-aramid fibers, polybenzimidazole fibers, polyetherketone fibers, polyethylene terephthalate fibers, and nylon fibers; semi-synthetic fibers such as acetate fibers and triacetate fibers; rayon fibers; regenerated fibers such as cuprammonium fibers; and plant fibers such as cotton, linen, and fibers containing wood as the main component. One or more of these may be used.

[0041] As the fibrillated fiber, in addition to the fiber obtained by fibrillating the above-mentioned fiber, pulp and the like can also be cited. One or more of these can be used. There is no particular limitation on the fibrillation method, and a common beating method can be adopted. As a representative example, a method of fibrillating using a beater (beater) and a refiner and other beaters (beaters) can be cited. In addition, when the fibrillated fiber is measured according to the Canadian Standard Filterability (CSF) of JIS P 8121-2, it is preferably 50 ml or more and less than 800 ml.

[0042] In the adsorption sheet of the present invention, the total content of the unfibrillated fibers and the fibrillated fibers is preferably 5% to 25% by mass, and more preferably 10% to 25% by mass. When the content is less than 5% by mass, it is difficult to fully load the porous metal complex on the adsorption sheet, the amount of shedding increases, and the strength of the sheet may be significantly reduced. On the other hand, when the content is greater than 25% by mass, it is sometimes difficult to obtain sufficient adsorption performance.

[0043] The adsorption sheet in the invention contains an organic binder. Because it will improve the softness and strength of the adsorption sheet. As an organic binder, there is no particular limitation as long as it can bond the porous metal complex and the fiber. For example, polyvinyl alcohol polymers, polyacrylonitrile polymers, polyethylene polymers, polyester polymers, polyphenylene ether polymers, etc. can be used. In terms of operability, polyvinyl alcohol polymers are preferred. The form of the organic binder is not particularly limited. If a fibrous substance is used, the adsorption sheet can be easily made, so it is preferred. The content of the organic binder in the adsorption sheet is preferably 3% to 15% by mass, and more preferably 4% to 12% by mass. When it is less than 3% by mass, the loadability of the porous metal complex and the softness of the sheet are insufficient. When it is greater than 15% by mass, the porous metal complex is covered by the organic binder, and there is a tendency that it is difficult to obtain sufficient adsorption performance.

[0044] The dissolution temperature of the organic binder in water is preferably 65°C to 100°C, more preferably 70°C to 100°C. When the dissolution temperature in water is less than 65°C, the ratio of the side chains of the binder entering the pores of the porous metal complex increases, resulting in a possibility that the adsorption performance becomes insufficient. In addition, due to insufficient bonding at a high temperature higher than 100°C, there is a problem of poor loadability.

[0045] The dissolution temperature of an organic binder in water can be measured by a common method. For example, there is the following method: 100 ml of pure water is placed in a beaker and stirred, and heated in an oil bath until the water temperature reaches 50°C, 0.5 g of an organic binder is added, and the water temperature is raised at a heating rate of 2°C / min, and the temperature at which the binder begins to dissolve and becomes translucent is measured by visual observation.

[0046] The adsorption sheet of the present invention is a material that exhibits load-bearing properties through fibrillated fibers and exhibits softness through the high water adsorption rate of the porous metal complex even if the content of the organic binder is small. As a result, sufficient adsorption performance can be exhibited by a small amount of organic binder and the high adsorption performance of the porous metal complex itself.

[0047] The absorbent sheet of the present invention preferably has a relative tensile elongation of 5%·m / g or more as an indicator of flexibility. If it is less than 5%·m / g, the sheet has poor flexibility and cracks may occur during honeycomb processing (segment processing).

[0048] The adsorption sheet of the present invention may contain one or more porous metal complexes, and may further contain porous materials other than porous metal complexes. The porous materials contained in the adsorption sheet of the present invention are not particularly limited, and examples thereof include organic polymer porous bodies such as activated carbon, zeolite, silica gel, activated alumina, aluminum phosphate, silicoaluminophosphate, and styrene-divinylbenzene copolymers. Activated carbon, zeolite, silica gel, and activated alumina that can be obtained at a low price are preferred.

[0049] The thickness of the adsorption sheet of the present invention is preferably 0.1 mm to 0.9 mm, and more preferably 0.1 mm to 0.7 mm. When the thickness is less than 0.1 mm, the strength of the sheet material is significantly reduced, so it is sometimes difficult to process it into an adsorption element such as a honeycomb shape during post-processing. In addition, if the thickness is greater than 0.9 mm, there is a tendency for the pressure loss of the adsorption element to increase when the adsorption sheet is processed into a honeycomb shape.

[0050] The weight of the adsorption sheet of the present invention is preferably 25 g / m 2 ~200g / m 2 More preferably 40g / m 2 ~150g / m 2 If the weight is less than 25g / m 2If the weight is greater than 200g / m 2 , the thickness of the sheet becomes too large, and the pressure loss of the adsorption element during processing such as honeycomb may increase.

[0051] There is no particular limitation on the method for manufacturing the adsorption sheet of the present invention, and any known processing method can be used. Preferably, a wet sheeting method can be exemplified, in which a porous metal complex, fibers and an organic binder are dispersed in water, an organic solvent or a mixture thereof, and the resultant is formed, dehydrated and dried to obtain the wet sheeting.

[0052] Here, the porous metal complex preferably has solvent molecules in its pores, and the materials constituting the above-mentioned sheet are mixed and supplied to the sheeting process. When the porous metal complex does not have solvent molecules in the pores, the organic binder constituting the adsorption sheet will be at risk of being adsorbed in the pores. At this time, after the sheeting, even if the desolventizing treatment described later is implemented, it is difficult to remove the organic binder captured in the pores of the porous metal complex, resulting in the deterioration of the adsorption performance of the adsorption sheet. That is, in the present invention, by making the pores of the porous metal complex adsorb solvent molecules, the organic binder in the sheeting process can be prevented from being adsorbed into the pores. After the sheeting process, the solvent molecules are removed from the pores by the desolventizing treatment described later to ensure the adsorption performance of the adsorption sheet. Usually, at the stage of synthesizing the porous metal complex, although the pores of the porous metal complex are adsorbed with solvent molecules, when the porous metal complex does not have solvent molecules in the pores or the adsorption amount of the solvent molecules is insufficient, the organic solvent can be adsorbed in the pores by the method described in the embodiments described later. Here, the solvent molecules refer to water and general organic solvent molecules.

[0053] When manufacturing the adsorption sheet of the present invention, after the sheeting process, a desolventizing process is performed to remove the solvent contained in the adsorption sheet. As described above, the porous metal complex is preferably sheeted in a state where there are solvent molecules in its pores. At this time, it is difficult to obtain sufficient adsorption performance due to the solvent molecules in the pores of the porous metal complex. Therefore, in order to show the adsorption performance, the desolventizing process is performed after the sheeting process. In addition, the implementation period of the desolventizing process is not particularly limited as long as it is after the sheeting process.

[0054] The conditions for the desolvation treatment are not particularly limited, and the temperature is preferably 50°C to 300°C. If it is less than 50°C, the removal of the solvent may not be complete, and sometimes it is difficult to obtain sufficient adsorption performance. On the other hand, if it is greater than 300°C, the pore structure of the porous metal complex may be destroyed, and it is also difficult to obtain sufficient adsorption performance. It is more preferably 80°C to 200°C. In addition, the desolvation treatment can be more effectively removed by carrying out the desolvation treatment under reduced pressure. At this time, the pressure is not particularly limited, as long as it is appropriately adjusted according to the physical properties of the porous metal complex and the mixing amount, for example, it is preferably 10 3 Pa~10 -5 Pa, more preferably 10 -1 Pa~10 -5 The desolvation treatment time is also not particularly limited, and is preferably 1 to 100 hours, more preferably 3 to 48 hours, and even more preferably 3 to 24 hours. In addition, the most preferred desolvation treatment conditions are: 80°C to 200°C under vacuum conditions for 3 to 24 hours.

[0055] The adsorption sheet of the present invention may be used in a flat plate shape, or may be appropriately subjected to pleating, honeycomb, corrugation, or the like to form a desired shape for use. Figure 1 As an example of processing the adsorbent sheet of the present invention, the adsorbent sheet 1 is processed into a wavy segment sheet. In particular, in the process of pleating, honeycomb, and corrugation, the sheet needs to be bent during processing. In this case, the porous metal complex is allowed to fully absorb water before processing, thereby showing the softness of the sheet. There is no particular limitation on the method of allowing the porous metal complex to absorb water, but a method of using a humidified room or processing while blowing steam is preferred because of its simplicity.

[0056] The adsorption element of the present invention is characterized in that it is provided with the adsorption sheet of the present invention. There is no particular limitation on the type of the adsorption element of the present invention, and any existing known type can be adopted, as long as it is appropriately selected according to the use and purpose. In addition, the shape of the adsorption sheet of the adsorption element of the present invention is not particularly limited, for example, an adsorption sheet processed into a flat shape, a pleated shape, a honeycomb shape, etc. can be used. For example, when the adsorption sheet processed into a pleated shape is used as a direct-current adsorption element, and when the adsorption sheet processed into a honeycomb shape is used as a parallel-flow adsorption element, the contact area with the treated gas can be increased to simultaneously achieve the improvement of the removal efficiency of the adsorption target substance and the low pressure loss of the adsorption element. Compared with the direct-current adsorption element, the parallel-flow adsorption element is excellent in preventing blockage caused by mist and garbage, low pressure loss, and lightweight, so the adsorption sheet of the adsorption element is preferably honeycomb-shaped.

[0057] Figure 2, as an example of the adsorption element of the present invention, a diagram of an adsorption rotor 2 in which the adsorption sheet of the present invention is wound into a rotor shape is shown. The adsorption sheet included in the adsorption rotor 2 has a honeycomb shape.

[0058] The adsorption sheet of the present invention and the adsorption element having the adsorption sheet can be widely used in houses, vehicles, wallpapers, furniture, interior materials, resin molded bodies, electrical equipment, etc. for the purpose of reducing odor components, separating and recovering organic solvents in the air discharged from factories, etc., or adjusting humidity / dehumidification.

[0059] In addition, an adsorption-desorption treatment device having an adsorption element of the present invention, an adsorption device for introducing an adsorption target substance into the adsorption element and adsorbing it, and a desorption device for desorbing the adsorption target substance adsorbed by the adsorption element is also included in the scope of the present invention. The adsorption device may be a tube for introducing air or gas containing odorous substances such as organic solvents and adsorption target substances such as water. As methods for desorbing the adsorption target substance, there are heating methods and methods for reducing the system pressure. As desorption devices, pipes or heaters for introducing heated gas, pressure reducers, etc. may be considered. For the sake of desorption efficiency and economy, a device for introducing heated air is preferred.

[0060] Figure 3 In the figure, a dehumidification air conditioning system 11 is shown as an example of the adsorption and desorption processing device of the present invention. The dehumidification air conditioning system 11 includes an adsorption rotor 2, a motor 3, a heat source 8 such as a heater, a fan 9, and a dehumidification / humidification area switching component 10. In the dehumidification air conditioning system 11, if a high-humidity gas 4 containing water as an adsorption target substance is introduced, the water is adsorbed to the adsorption rotor 2 and discharged as a dehumidified gas 5. If a low-humidity gas 6 heated by the heat source 8 is introduced, the water adsorbed in the adsorption rotor 2 is desorbed and discharged as a humidified gas 7. The adsorption and desorption processing device of the present invention is suitable for dehumidification air conditioning systems for factories, and is also suitable for dehumidification air conditioning systems for households.

[0061] [Example]

[0062] The present invention will be described in more detail below by way of examples. In addition, the following examples are not examples that limit the nature of the present invention, and any design changes made based on the principles described above are included in the technical scope of the present invention.

[0063] First, the measuring methods and evaluation methods of the characteristic values ​​obtained in Examples and Comparative Examples are as follows.

[0064] [Water adsorption rate]

[0065] Take about 100 mg of the porous metal complex (before treatment with water or an organic solvent), dry it in a vacuum at 120°C for 12 hours, and then weigh it. Use a high-precision gas vapor adsorption measuring device (BELSORP-max, manufactured by Bel Co., Ltd., Japan) to measure the adsorption of water vapor at 25°C at 40 points while slowly increasing the relative pressure in the range of 0.02 to 0.95, and make an adsorption isotherm. At this time, set the target relative pressure to 0.001, 0.01, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, and further set the adsorption amount increase and decrease allowable capacity to 30 cm at a relative pressure of 0 to 0.3. 2 / g, set to 50cm at relative pressure of 0.3 to 0.5 2 / g, set to 30cm at relative pressure 0.5~ 2 / g, and an adsorption isotherm was prepared. Then, the water adsorption rate [%] was calculated from the amount of water adsorbed per 1g of the porous metal complex at a relative pressure of 0.5 [g] using the following formula (i).

[0066] Water adsorption rate [%] = Water adsorption amount per 1g of adsorbent [g] × 100... (i)

[0067] [BET specific surface area]

[0068] Take about 100 mg of the porous metal complex (before water or organic solvent treatment), vacuum dry it at 120°C for 12 hours, and weigh it. Use an automatic specific surface area measuring device (Gemini 2375, manufactured by Micromeritics) to measure the adsorption of nitrogen at the boiling point of liquid nitrogen (-195.8°C) at 40 points while slowly increasing the relative pressure in the range of 0.02 to 0.95, and make an adsorption isotherm. Use the analysis software (GEMINI-PCW version 1.01) attached to the automatic specific surface area measuring device, set the surface area analysis range to 0.01 to 0.15 under BET conditions, and obtain the BET specific surface area [m 2 / g].

[0069] [Load capacity]

[0070] A 10cm×10cm test piece cut from the adsorption sheet sample was fixed vertically on the laboratory table with a 10cm×10cm flat portion, and a sphere (raw material: aluminum) with a diameter of 2.4cm and a mass of 20g was vertically hit 10 times against the 10cm×10cm flat portion of the test piece. The sphere rolled at a speed of 10cm / s. As a result, when the amount of porous metal complex detached was less than 0.1mg, it was set to ○ (good), when it was more than 10mg, it was set to × (bad), and when it was 0.1mg to 10mg, it was set to △ (acceptable).

[0071] [Softness]

[0072] Regarding flexibility, in Examples and Comparative Examples, it was observed whether cracks were generated when the adsorption sheet was subjected to honeycomb processing (segment processing).

[0073] A 10 cm x 10 cm test piece cut from the adsorption sheet sample was dried at 120°C for 1 hour, and then allowed to stand at 22°C and 40% RH for 1 hour. The two ends of the test piece conditioned in this way were held and bent 90 degrees. At this time, the sheet was evaluated as ○ (good) if no cracks occurred, △ (difficult) if cracks occurred, and × (poor) if cracks occurred.

[0074] [Relative tensile elongation]

[0075] A 15 mm × 100 mm test piece cut from the adsorption sheet sample was dried at 120°C for 1 hour, and its weight was measured. Then, the dried sample was allowed to stand for 1 hour in an atmosphere of 22°C and 40% RH, and the maximum point elongation [%] was measured using a tensile-compression tester (TENSILON RTG-1310, manufactured by A&D). In addition, the distance between the clamps was set to 50 mm and the tensile speed was set to 15 mm / min. Based on the obtained data, the relative tensile elongation was calculated using the following formula (ii).

[0076] Relative tensile elongation [%·m / g] = maximum elongation [%] / sample width [m] / weight of absorbent sheet [g / m 2 ]…(ii)

[0077] [Pore maintenance rate]

[0078] Take about 100 mg of the adsorption sheet sample, dry it in vacuum at 120°C for 12 hours, and then weigh it. Use an automatic specific surface area measuring device (Gemini 2375, manufactured by Micromeritics) to slowly increase the adsorption amount of nitrogen gas at the boiling point of liquid nitrogen (-195.8°C) in the relative pressure range of 0.02 to 0.95 while measuring 40 points to make the adsorption isotherm of the sample. Use the analysis software (GEMINI-PCW version1.01) attached to the automatic specific surface area measuring device, set the surface area analysis range to 0.01 to 0.15 under BET conditions, and calculate the BET specific surface area [m 2 / g]. Then, based on the BET specific surface area [m 2 / g], and the pore maintenance rate was calculated by the following formula (iii).

[0079] Pore ​​maintenance rate [%] = {BET specific surface area of ​​adsorption sheet [m 2 / g]×100 / (content of porous metal complex in adsorption sheet)} / (BET specific surface area of ​​porous metal complex sample [m 2 / g])×100…(iii)

[0080] The higher the pore maintenance rate is, the more the pores of the porous metal complex are not filled with a binder or the like (the pores are not blocked), and the higher the adsorption performance is.

[0081] [Sheet properties (water vapor adsorption)]

[0082] Take about 100 mg of the porous metal complex (before water or organic solvent treatment), vacuum dry it at 120°C for 12 hours, and then weigh it. Use a high-precision gas vapor adsorption measuring device (BELSORP-max, made by Bel Co., Ltd., Japan) to measure the adsorption of water vapor at 25°C at 40 points while slowly increasing the relative pressure range of 0.02 to 0.95, and make an adsorption isotherm. Then, the water vapor adsorption per 1g of the porous metal complex at a relative pressure of 0.95 [ml] is obtained. As an evaluation of the sheet performance, the water vapor adsorption is evaluated as ○ (good) for a water vapor adsorption of 410ml / g or more, △ (acceptable) for a water vapor adsorption of more than 400ml / g and less than 410ml / g, and × (poor) for a water vapor adsorption of less than 400ml / g.

[0083] [Processability]

[0084] As for the processability, in Examples and Comparative Examples, whether or not the segment shape can be maintained by itself after segment processing was observed.

[0085] The adsorbent sheet sample was made into a 30 cm wide x 30 cm long sheet and passed through a corrugating machine that can theoretically produce corrugated paper of 30 cm wide x 21.4 cm long. The corrugated adsorbent sheet was then left to stand for 24 hours in an atmosphere of 22°C and 40% RH, and evaluated by ○ (good) for a length recovery rate of less than 20%, △ (acceptable) for 20% to less than 50%, and × (bad) for 50% to 100%.

[0086] [Dissolution temperature in water]

[0087] The dissolution temperatures of the organic binders used in the examples and comparative examples were measured in water by the following method, and all of them were the same as the catalog values, except for the organic binder of Example 8. The catalog value of the organic binder of Example 8 was <99°C, and the measured value was 95°C.

[0088] Put 4 mL of pure water and 0.02 g of an organic binder into a 6 mL glass bottle. Put the glass bottle into a water bath heated at 50°C for 10 minutes. Stir the organic binder in the bottle with a spatula every 2 minutes. Visually measure the temperature at which the binder begins to dissolve and becomes translucent.

[0089] <Example 1>

[0090] 16.2 g (40 mmol) of Fe(NO3)3·9H2O and 7.5 g (36 mmol) of trimesic acid were dissolved in 32 ml of water and heated at 95°C for 15 hours to synthesize a porous metal complex. The physical properties of the obtained porous metal complex were evaluated by nitrogen adsorption measurement and water vapor adsorption measurement. The results showed that the BET specific surface area was 1575 m 2 / g, and the moisture adsorption rate is 53%.

[0091] Then, the synthesized porous metal complex is immersed in water for 24 hours and filtered to obtain a porous metal complex sample in which solvent molecules are adsorbed in the pores. 80% by mass of the porous metal complex sample (excluding solvent molecules), 8% by mass of aramid fiber as unfibrillated fiber, 5% by mass of aramid fiber as fibrillated fiber, and 7% by mass of polyvinyl alcohol (PVA) fiber with a water dissolution temperature of 70°C (catalog value) as an organic binder are mixed in a ratio of 100 g / m 2 The mass of the adsorbent sheet was prepared using a wet papermaking device (manufactured by Toyobo Engineering Co., Ltd., the same below). Furthermore, the adsorbent sheet sample was obtained by desolventizing at 130°C under vacuum conditions for 24 hours. The loadability, softness, pore maintenance rate, water vapor adsorption performance, and processability of the obtained sample were measured.

[0092] <Example 2>

[0093] 80% by weight (excluding solvent molecules) of the porous metal complex sample obtained in the same manner as in Example 1, 10% by weight of aramid fiber as unfibrillated fiber, 3% by weight of aramid fiber as fibrillated fiber, and 7% by weight of polyvinyl alcohol (PVA) fiber having a water dissolution temperature of 70°C (catalog value) as an organic binder were mixed to give a gram weight of 100 g / m 2 The adsorption sheet was made by using a wet papermaking device. Furthermore, the adsorption sheet sample was obtained by desolventizing at 130°C under vacuum for 24 hours. The loadability, softness, pore maintenance rate, water vapor adsorption performance, and processability of the obtained sample were measured.

[0094] <Example 3>

[0095] 80% by weight (excluding solvent molecules) of the porous metal complex sample obtained in the same manner as in Example 1, 8% by weight of aramid fiber as unfibrillated fiber, 7% by weight of aramid fiber as fibrillated fiber, and 5% by weight of polyvinyl alcohol (PVA) fiber having a water dissolution temperature of 70°C (catalog value) as an organic binder were mixed to give a gram weight of 100 g / m 2 The adsorption sheet was made by using a wet papermaking device. Furthermore, the adsorption sheet sample was obtained by desolventizing at 130°C under vacuum for 24 hours. The loadability, softness, pore maintenance rate, water vapor adsorption performance, and processability of the obtained sample were measured.

[0096] <Example 4>

[0097] 80% by weight (excluding solvent molecules) of the porous metal complex sample obtained in the same manner as in Example 1, 8% by weight of aramid fiber as unfibrillated fiber, 9% by weight of aramid fiber as fibrillated fiber, and 3% by weight of polyvinyl alcohol (PVA) fiber having a water dissolution temperature of 70°C (catalog value) as an organic binder were mixed to give a gram weight of 100 g / m 2 The adsorption sheet was made by using a wet papermaking device. Furthermore, the adsorption sheet sample was obtained by desolventizing at 130°C under vacuum for 24 hours. The loadability, softness, pore maintenance rate, water vapor adsorption performance, and processability of the obtained sample were measured.

[0098] <Example 5>

[0099] The porous metal complex sample obtained in the same manner as in Example 1 was mixed in a ratio of 75% by mass (excluding solvent molecules), 10% by mass of aramid fiber as unfibrillated fiber, 6.3% by mass of aramid fiber as fibrillated fiber, and 8.7% by mass of polyvinyl alcohol (PVA) fiber having a water dissolution temperature of 70°C (catalog value) as an organic binder to give a gram weight of 100 g / m 2 The adsorption sheet was made by using a wet papermaking device. Furthermore, the adsorption sheet sample was obtained by desolventizing at 130°C under vacuum for 24 hours. The loadability, softness, pore maintenance rate, water vapor adsorption performance, and processability of the obtained sample were measured.

[0100] <Example 6>

[0101] The porous metal complex sample obtained in the same manner as in Example 1 was mixed in a ratio of 70% by mass (excluding solvent molecules), 12% by mass of aramid fiber as unfibrillated fiber, 7.5% by mass of aramid fiber as fibrillated fiber, and 10.5% by mass of polyvinyl alcohol (PVA) fiber having a water dissolution temperature of 70°C (catalog value) as an organic binder to give a gram weight of 100 g / m 2 The adsorption sheet was made by using a wet papermaking device. Furthermore, the adsorption sheet sample was obtained by desolventizing at 130°C under vacuum for 24 hours. The loadability, softness, pore maintenance rate, water vapor adsorption performance, and processability of the obtained sample were measured.

[0102] <Example 7>

[0103] The porous metal complex sample obtained in the same manner as in Example 1 was mixed in a ratio of 65 mass % (excluding solvent molecules), 14 mass % of aramid fiber as unfibrillated fiber, 8.8 mass % of aramid fiber as fibrillated fiber, and 12.2 mass % of polyvinyl alcohol (PVA) fiber having a water dissolution temperature of 70° C. (catalog value) as an organic binder to give a gram weight of 100 g / m 2 The adsorption sheet was made by using a wet papermaking device. Furthermore, the adsorption sheet sample was obtained by desolventizing at 130°C under vacuum for 24 hours. The loadability, softness, pore maintenance rate, water vapor adsorption performance, and processability of the obtained sample were measured.

[0104] <Example 8>

[0105] The porous metal complex sample obtained in the same manner as in Example 1 was mixed in a ratio of 65 mass % (excluding solvent molecules), 14 mass % of aramid fiber as unfibrillated fiber, 8.8 mass % of aramid fiber as fibrillated fiber, and 12.2 mass % of polyvinyl alcohol (PVA) fiber having a solubility temperature in water of <99°C (indicating that it begins to melt just before water boils, a catalog value) as an organic binder, and the mixture was mixed to a weight of 100 g / m 2 The adsorption sheet was made by using a wet papermaking device. Furthermore, the adsorption sheet sample was obtained by desolventizing at 130°C under vacuum for 24 hours. The loadability, softness, pore maintenance rate, water vapor adsorption performance, and processability of the obtained sample were measured.

[0106] <Example 9>

[0107] 80% by weight (excluding solvent molecules) of the porous metal complex sample obtained in the same manner as in Example 1, 8% by weight of rayon fibers as unfibrillated fibers, 5% by weight of rayon fibers as fibrillated fibers, and 7% by weight of polyvinyl alcohol (PVA) fibers having a water dissolution temperature of 70° C. (catalog value) as an organic binder were mixed to give a gram weight of 100 g / m 2 The adsorption sheet was made by using a wet papermaking device. Furthermore, the adsorption sheet sample was obtained by desolventizing at 130°C under vacuum for 24 hours. The loadability, softness, pore maintenance rate, water vapor adsorption performance, and processability of the obtained sample were measured.

[0108] <Example 10>

[0109] The porous metal complex sample obtained in the same manner as in Example 1 was mixed in a ratio of 80% by weight (excluding solvent molecules), 8% by weight of PET fibers as unfibrillated fibers, 5% by weight of aramid fibers as fibrillated fibers, and 7% by weight of polyvinyl alcohol (PVA) fibers having a water dissolution temperature of 70° C. (catalog value) as an organic binder to give a gram weight of 100 g / m 2 The adsorption sheet was made by using a wet papermaking device. Furthermore, the adsorption sheet sample was obtained by desolventizing at 130°C under vacuum for 24 hours. The loadability, softness, pore maintenance rate, water vapor adsorption performance, and processability of the obtained sample were measured.

[0110] <Example 11>

[0111] Basolite C300 (manufactured by BASF) was used as the porous metal complex. Physical properties were evaluated by nitrogen adsorption measurement and water vapor adsorption measurement. As a result, the BET specific surface area was 1609 m 2 / g, and the moisture adsorption rate is 43%.

[0112] Then, the porous metal complex was immersed in N,N-dimethylformaldehyde for 24 hours and filtered to obtain a porous metal complex sample in which solvent molecules were adsorbed in the pores. 80% by mass of the porous metal complex sample (excluding solvent molecules), 8% by mass of aramid fiber as unfibrillated fiber, 5% by mass of aramid fiber as fibrillated fiber, and 7% by mass of polyvinyl alcohol (PVA) fiber with a water dissolution temperature of 70°C (catalog value) as an organic binder were mixed in a ratio of 100 g / m 2The adsorption sheet was made by using a wet papermaking device. Furthermore, the adsorption sheet sample was obtained by desolventizing at 130°C under vacuum for 24 hours. The loadability, softness, pore maintenance rate, water vapor adsorption performance, and processability of the obtained sample were measured.

[0113] <Example 12>

[0114] 3 ml (10 mmol) of tetraisopropyl titanate and 2.5 g (15 mmol) of terephthalic acid were dissolved in 45 ml of N,N-dimethylformaldehyde and 5 ml of methanol, and heated at 150°C for 15 hours to synthesize a porous metal complex. The physical properties of the obtained porous metal complex were evaluated by nitrogen adsorption measurement and water vapor adsorption measurement. The results showed that the BET specific surface area was 1199 m 2 / g, and the moisture adsorption rate is 38%.

[0115] Then, the porous metal complex synthesized above was immersed in N,N-dimethylformaldehyde for 24 hours and filtered to obtain a porous metal complex sample in which solvent molecules were adsorbed in the pores. 80% by mass of the porous metal complex sample (excluding solvent molecules), 8% by mass of aramid fiber as unfibrillated fiber, 5% by mass of aramid fiber as fibrillated fiber, and 7% by mass of polyvinyl alcohol (PVA) fiber with a water dissolution temperature of 70°C (catalog value) as an organic binder were mixed in a ratio of 100 g / m 2 The adsorption sheet was made by using a wet papermaking device. Furthermore, the adsorption sheet sample was obtained by desolventizing at 130°C under vacuum for 24 hours. The loadability, softness, pore maintenance rate, water vapor adsorption performance, and processability of the obtained sample were measured.

[0116] <Example 13>

[0117] 5.3 g (22.7 mmol) of zirconium chloride and 3.78 g (22.8 mmol) of terephthalic acid were dissolved in 500 ml of N,N-dimethylformaldehyde and heated at 120°C for 24 hours to synthesize a porous metal complex. The physical properties of the obtained porous metal complex were evaluated by nitrogen adsorption measurement and water vapor adsorption measurement. The results showed that the BET specific surface area was 1283 m 2 / g, and the moisture adsorption rate is 42%.

[0118] Then, the synthesized porous metal complex is immersed in water for 24 hours and filtered to obtain a porous metal complex sample in which solvent molecules are adsorbed in the pores. 80% by mass of the porous metal complex sample (excluding solvent molecules), 8% by mass of aramid fiber as unfibrillated fiber, 5% by mass of aramid fiber as fibrillated fiber, and 7% by mass of polyvinyl alcohol (PVA) fiber with a water dissolution temperature of 70°C (catalog value) as an organic binder are mixed in a ratio of 100 g / m 2 The adsorption sheet was made by using a wet papermaking device. Furthermore, the adsorption sheet sample was obtained by desolventizing at 130°C under vacuum for 24 hours. The loadability, softness, pore maintenance rate, water vapor adsorption performance, and processability of the obtained sample were measured.

[0119] <Example 14>

[0120] 80% by weight (excluding solvent molecules) of the porous metal complex sample obtained in the same manner as in Example 14, 9.2% by weight of aramid fiber as unfibrillated fiber, 5.8% by weight of aramid fiber as fibrillated fiber, and 5% by weight of polyvinyl alcohol (PVA) fiber having a solubility temperature in water of 70°C (catalog value) as an organic binder were mixed in a ratio of 100 g / m 2 The adsorption sheet was made by using a wet papermaking device. Furthermore, the adsorption sheet sample was obtained by desolventizing at 130°C under vacuum for 24 hours. The loadability, softness, pore maintenance rate, water vapor adsorption performance, and processability of the obtained sample were measured.

[0121] <Example 15>

[0122] 200 g (0.62 mol) of ZrOCl2·8H2O and 72 g (0.62 mol) of fumaric acid were dissolved in 2 L of N,N-dimethylformaldehyde and 700 mL of formic acid, and heated at 130°C for 6 hours to synthesize a porous metal complex. The physical properties of the obtained porous metal complex were evaluated by nitrogen adsorption measurement and water vapor adsorption measurement. The results showed that the BET specific surface area was 884 m 2 / g, and the moisture adsorption rate is 33%.

[0123] Then, the synthesized porous metal complex is immersed in water for 24 hours and filtered to obtain a porous metal complex sample in which solvent molecules are adsorbed in the pores. 80% by mass of the porous metal complex sample (excluding solvent molecules), 8% by mass of aramid fiber as unfibrillated fiber, 5% by mass of aramid fiber as fibrillated fiber, and 7% by mass of polyvinyl alcohol (PVA) fiber with a water dissolution temperature of 70°C (catalog value) as an organic binder are mixed in a ratio of 100 g / m 2 The adsorption sheet was made by using a wet papermaking device. Furthermore, the adsorption sheet sample was obtained by desolventizing at 130°C under vacuum for 24 hours. The loadability, softness, pore maintenance rate, water vapor adsorption performance, and processability of the obtained sample were measured.

[0124] <Example 16>

[0125] 12.87 g (55.2 mmol) of zirconium chloride and 9.45 g (52.5 mmol) of 2-aminoterephthalic acid were dissolved in 600 mL of N,N-dimethylformaldehyde and heated at 120°C for 24 hours to synthesize a porous metal complex. The physical properties of the obtained porous metal complex were evaluated by nitrogen adsorption measurement and water vapor adsorption measurement. The results showed that the BET specific surface area was 949 m 2 / g, and the moisture adsorption rate is 32%.

[0126] Then, the synthesized porous metal complex is immersed in water for 24 hours and filtered to obtain a porous metal complex sample in which solvent molecules are adsorbed in the pores. 80% by mass of the porous metal complex sample (excluding solvent molecules), 8% by mass of aramid fiber as unfibrillated fiber, 5% by mass of aramid fiber as fibrillated fiber, and 7% by mass of polyvinyl alcohol (PVA) fiber with a water dissolution temperature of 70°C (catalog value) as an organic binder are mixed in a ratio of 100 g / m 2 The adsorption sheet was made by using a wet papermaking device. Furthermore, the adsorption sheet sample was obtained by desolventizing at 130°C under vacuum for 24 hours. The loadability, softness, pore maintenance rate, water vapor adsorption performance, and processability of the obtained sample were measured.

[0127] <Example 17>

[0128] 3.6 ml (12.3 mmol) of tetraisopropyl titanate and 3.6 g (19.9 mmol) of 2-aminoterephthalic acid were dissolved in 48 ml of N,N-dimethylformamide and 12 ml of methanol, and heated at 150°C for 18 hours to synthesize a porous metal complex. The physical properties of the obtained porous metal complex were evaluated by nitrogen adsorption measurement and water vapor adsorption measurement. The results showed that the BET specific surface area was 1248 m 2 / g, and the moisture adsorption rate is 43%.

[0129] Then, the synthesized porous metal complex is immersed in water for 24 hours and filtered to obtain a porous metal complex sample in which solvent molecules are adsorbed in the pores. 80% by mass of the porous metal complex sample (excluding solvent molecules), 8% by mass of aramid fiber as unfibrillated fiber, 5% by mass of aramid fiber as fibrillated fiber, and 7% by mass of polyvinyl alcohol (PVA) fiber with a water dissolution temperature of 70°C (catalog value) as an organic binder are mixed in a ratio of 100 g / m 2 The adsorption sheet was made by using a wet papermaking device. Furthermore, the adsorption sheet sample was obtained by desolventizing at 130°C under vacuum for 24 hours. The loadability, softness, pore maintenance rate, water vapor adsorption performance, and processability of the obtained sample were measured.

[0130] <Comparative Example 1>

[0131] Aluminum nitrate 15g (40mmol) and 1,4-naphthalenedicarboxylic acid 4.32g (20mmol) were dissolved in 400ml of water and heated at 180°C for 24 hours to synthesize a porous metal complex. The physical properties of the obtained porous metal complex were evaluated by nitrogen adsorption measurement and water vapor adsorption measurement. The results showed that the BET specific surface area was 639m 2 / g, and the moisture adsorption rate is 17%.

[0132] Then, the synthesized porous metal complex is immersed in water for 24 hours and filtered to obtain a porous metal complex sample in which solvent molecules are adsorbed in the pores. 80% by mass of the porous metal complex sample (excluding solvent molecules), 8% by mass of aramid fiber as fibrillated fiber, 5% by mass of aramid fiber as fibrillated fiber, and 7% by mass of polyvinyl alcohol (PVA) fiber with a water dissolution temperature of 70°C (catalog value) as an organic binder are mixed in a ratio of 100 g / m 2 The adsorption sheet was made by using a wet papermaking device. Furthermore, the adsorption sheet sample was obtained by desolventizing at 130°C under vacuum for 24 hours. The loadability, softness, pore maintenance rate, water vapor adsorption performance, and processability of the obtained sample were measured.

[0133] <Comparative Example 2>

[0134] 80% by weight (excluding solvent molecules) of the porous metal complex sample obtained in the same manner as in Example 1, 8% by weight of aramid fiber as unfibrillated fiber, 5% by weight of aramid fiber as fibrillated fiber, and 7% by weight of polyvinyl alcohol (PVA) fiber having a water dissolution temperature of 60° C. (catalog value) as an organic binder were mixed to give a gram weight of 100 g / m 2 The adsorption sheet was made by using a wet papermaking device. Furthermore, the adsorption sheet sample was obtained by desolventizing at 130°C under vacuum for 24 hours. The loadability, softness, pore maintenance rate, water vapor adsorption performance, and processability of the obtained sample were measured.

[0135] <Comparative Example 3>

[0136] The porous metal complex sample obtained in the same manner as in Example 1 was mixed in a ratio of 65 mass % (excluding solvent molecules), 14 mass % of aramid fiber as unfibrillated fiber, 8.8 mass % of aramid fiber as fibrillated fiber, and 12.2 mass % of polyvinyl alcohol (PVA) fiber having a water solubility temperature of >100°C (indicating that it does not dissolve after boiling water, a catalog value) as an organic binder, and the mixture was mixed to a weight of 100 g / m 2 The adsorption sheet was made by using a wet papermaking device. Furthermore, the adsorption sheet sample was obtained by desolventizing at 130°C under vacuum for 24 hours. The loadability, softness, pore maintenance rate, water vapor adsorption performance, and processability of the obtained sample were measured.

[0137] <Comparative Example 4>

[0138] 80% by weight (excluding solvent molecules) of the porous metal complex sample obtained in the same manner as in Example 1, 13% by weight of aramid fiber as fibrillated fiber, and 7% by weight of polyvinyl alcohol (PVA) fiber having a water dissolution temperature of 70° C. as an organic binder were mixed to give a gram weight of 100 g / m 2 The adsorption sheet was made by using a wet papermaking device. In addition, unfibrillated fibers were not used in this comparative example. The adsorption sheet made as described above was further subjected to a desolventizing treatment at 130°C under vacuum conditions for 24 hours to obtain an adsorption sheet sample. The loadability, softness, pore maintenance rate, water vapor adsorption performance, and processability of the obtained sample were measured.

[0139] <Comparative Example 5>

[0140] 80% by weight (excluding solvent molecules) of the porous metal complex sample obtained in the same manner as in Example 1, 13% by weight of aramid fiber as unfibrillated fiber, and 7% by weight of polyvinyl alcohol (PVA) fiber having a water dissolution temperature of 70° C. (catalog value) as an organic binder were mixed to give a gram weight of 100 g / m 2 The adsorption sheet was made by using a wet papermaking device. In addition, unfibrillated fibers were not used in this comparative example. The adsorption sheet made as described above was further subjected to a desolventizing treatment at 130°C under vacuum conditions for 24 hours to obtain an adsorption sheet sample. The loadability, softness, pore maintenance rate, water vapor adsorption performance, and processability of the obtained sample were measured.

[0141] <Comparative Example 6>

[0142] A-type silica gel (manufactured by Toyota Chemical Industry Co., Ltd.) was used as the adsorbent. Physical properties were evaluated by nitrogen adsorption measurement and water vapor adsorption measurement. As a result, the BET specific surface area was 820 m 2 / g, moisture adsorption rate is 25%.

[0143] Then, the adsorbent material was immersed in water for 24 hours and filtered to obtain an adsorbent sample with solvent molecules adsorbed in the pores. 80% by weight of the adsorbent sample (excluding solvent molecules), 8% by weight of aramid fiber as unfibrillated fiber, 5% by weight of aramid fiber as fibrillated fiber, and 7% by weight of polyvinyl alcohol (PVA) fiber with a water dissolution temperature of 70°C (catalog value) as an organic binder were mixed in a ratio of 100 g / m 2 The adsorption sheet was made by using a wet papermaking device. Furthermore, the adsorption sheet sample was obtained by desolventizing at 130°C under vacuum for 24 hours. The loadability, softness, pore maintenance rate, water vapor adsorption performance, and processability of the obtained sample were measured.

[0144] Tables 1 to 5 show the measurement results of the adsorption sheet samples obtained in Examples 1 to 17 and Comparative Examples 1 to 6.

[0145]

[0146]

[0147]

[0148]

[0149] As can be seen from Tables 1 to 5, the adsorption sheets of Examples 1 to 17 are excellent in supporting properties of the porous metal complex and in the flexibility and processability of the sheets, and have sufficient adsorption performance.

[0150]

Industrial Applicability

[0151] The adsorption sheet, adsorption element, and adsorption-desorption treatment device of the present invention can efficiently separate and recover or adsorb and remove adsorption target substances such as water, organic solvents, and malodorous components. Therefore, it is expected that it will make a great contribution to the industry.

Claims

1. An adsorption sheet, characterized in that: The invention relates to a porous metal complex and unfibrillated fibers and fibrillated fibers, wherein the porous metal complex is composed of a compound having aluminum ions, zirconium ions or iron ions and an organic ligand, and the water adsorption rate at 25° C. and a relative pressure of 0.5 is 30% by mass or more, and the fiber diameter of the unfibrillated fibers is 5 μm to 30 μm, and the fiber length is 1 mm to 10 mm. The fibrillated fibers are one or more selected from the group consisting of glass fibers, ceramic fibers, rock wool fibers, aramid fibers, polybenzimidazole fibers, polyetherketone fibers, polyethylene terephthalate fibers, and nylon fibers fibrillated.

2. The adsorption sheet according to claim 1, characterized in that: The unfibrillated fibers are one or more selected from glass fibers, ceramic fibers, rock wool fibers, aramid fibers, polybenzimidazole fibers, polyetherketone fibers, polyethylene terephthalate fibers, nylon fibers, acetate fibers, rayon fibers, cuprammonium fibers, cotton, linen, and fibers with wood as the main component.

3. The adsorption sheet according to claim 1 or 2, characterized in that: Contains an organic binder with a dissolution temperature in water of 65°C to 100°C.

4. The adsorption sheet according to claim 1 or 2, characterized in that: The relative tensile elongation is above 5% m / g.

5. The adsorption sheet according to claim 1 or 2, characterized in that: The porous metal complex is contained in an amount of 60 to 85% by mass.

6. An adsorption element, characterized in that: A suction sheet according to any one of claims 1 to 5.

7. An adsorption-desorption treatment device, characterized in that: A device comprising the adsorption element according to claim 6, An adsorption device for introducing an adsorption target substance into the adsorption element and adsorbing the substance, and a desorption device for desorbing the adsorption target substance adsorbed by the adsorption element, so as to continuously perform adsorption and desorption of the adsorption target substance.

8. The adsorption sheet according to claim 1 or 2, characterized in that: The aramid fiber is meta-aramid fiber.

9. The adsorption sheet according to claim 2, characterized in that: The acetate fiber is triacetate fiber.

Citation Information

Patent Citations

  • Porous complex, its production and adsorbent

    JP2000327628A

  • New three-dimensional organometallic complex and gas adsorptive material

    JP2001348361A

  • Porous coordination polymer and application of the same

    JP2007051112A

  • Sheetlike products and works

    CN101484636A

  • Adsorption element and manufacturing method therefor

    JP2002239329A